Exploring indigenous intellectual property rights and e-governance: a legal analysis of customary aboriginal knowhow in Arunachal Pradesh, India - Rakshit, Partha Sarothi; Roy, Koyel; Bhowmik, Sarbani; Singhania, Saroj; Gosh, Aarin; Hossain, Syed Raihanul; Saha, Debanjan (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
The research study examines the legal protection of clan-based aboriginal healing processes, handicrafts, and unique creative works, which have been undermined from the ab initio. The government should shield the interests of their customary know-how under the IPR approach and community-based legal shields and documentation in the e-database. The research aims to investigate conventional aboriginal know-how practices of the Galo clan and e-governance meadow relating to the CAK issue and recommend lawful aspects. The researchers surveyed and collected information from 46 houses in Aalo town, Darka village, and Kabu village in West Siang District and Basar District in Arunachal Pradesh, the primary sources. The paper reports on findings from a study conducted in Arunachal Pradesh, India, to assess attitudes towards customary Aboriginal know-how (CAK) and its conservation. The survey demonstrates multiple views regarding the significance of safeguarding CAK through intellectual property rights (IPR) laws, traditional knowledge's role in socio-economic development, and whether e-governance can effectively help preserve CAK. In conclusion, a delicate balance must be between preserving traditional Galo practices and embracing modernity. A structured survey questionnaire collects quantitative data on attitudes, perceptions, and practices related to customary aboriginal know-how (CAK) conservation and legal protection. The questionnaire includes closed-ended questions to elicit specific responses from the informants regarding their views on safeguarding CAK, the role of intellectual property rights (IPR) laws, and the potential of e-governance in preserving CAK.